Iron overload and chelation modulates bisretinoid levels in the retina - Zhao, Jin; Kim, Hye Jin; Montenegro, Diego; Dunaief, Josh L.; Sparrow, Janet R. (Frontiers in Ophthalmology, 2023)
Aim: Iron dysregulation in conjunction with other disease processes may exacerbate retinal degeneration. We employed models of iron overload and iron chelation to explore interactions between iron-catalyzed oxidation and photoreactive bisretinoid lipofuscin.Methods: Mice were injected intravitreally with ferric ammonium citrate (FAC) or were treated with the iron chelator deferiprone (DFP) from birth to 2 months of age. Short-wavelength fundus autofluorescence (SW-AF) and spectral domain optical coherence tomography (SD-OCT) scans were acquired. Bisretinoids were quantified by ultra pressure liquid chromatography (UPLC) and in vivo by quantitative fundus autofluorescence (qAF). In histological sections photoreceptor cell viability was assessed by measuring the thickness of outer nuclear layer (ONL).Results: Levels of the bisretinoids all-trans-retinal dimer and A2PE were significantly increased in the FAC-injected eyes of C57BL/6J mice. Seven days after FAC-injection hyperautofluorescent foci were visible in fundus autofluorescence (488 nm) images and in spectral-domain optical coherence tomographic scans (SD-OCT), aberrant hyperreflectivity was present in outer retina. ONL thinning was observed. In FAC-injected Abca4 -/-mice having pronounced RPE bisretinoid lipofuscin accumulation the hyperautofluorescent puncta were more abundant than in wild-type mice and ONL thinning was greater. Conversely, intravitreal injection of FAC in Mertk -/-mice led to a more modest increase in A2PE after 2 days. In contrast to the effect of iron accumulation, chelation with DFP resulted in significantly increased A2E, A2-GPE and qAF due to reduced ironcatalyzed oxidation of bisretinoid. In Mertk -/-mice, A2E was significantly lower in DFP-treated mice and ONL area was reduced. DFP-chelation did not impair the visual cycle in BALB/cJ mice.Iron accumulation was associated with progressive impairment in photoreceptor cells that was associated with increased formation of a bisretinoid species known to form in